Therapeutic assessment as a brief and intensive intervention for avoidant restrictive food intake disorder, belching, and histrionic personality disorder: A case report (Indian Journal of Case Reports, 2024)
A 26-year-old female was hospitalized with complaints of repeated vomiting and weight loss (18 kg in 8 months); and incessant belching and nausea/regurgitation for 30 days subsequent to her COVID-19 treatment. After all the normal medical radiological reports, appropriate psychological and psychiatric evaluations were done. Incessant belching warranted a simple and flexible cognitive psychotherapy for histrionic personality with a therapeutic assessment technique. A total of 6 h of psychotherapy was delivered in three sessions. The belching and vomiting came down by 75% after the first extensive session, and almost 100% after the second session. However, mild belching reappeared, and after the termination-cum-booster session belching subsided till discharge and the first follow-up after 2 weeks.